Do morphometric measurements allow sex discrimination in Mockingbirds (Mimus sp)? - Fuchs, Daniela Viviana (2016)
Sexual dimorphism in birds may be expressed as differences in body size, plumage, color and/or behavior. Many species are monomorphic in color, making sex determination difficult in the field. An example of the latter are mockingbirds, which are passerines of the genus Mimus, endemic to the Americas. In order to distinguish between male and female mockingbirds using external body measurements that are easy to take, the objective of this work was to quantify morphometric differences between sexes in adults of the following species: M. thenca (45 specimens), M. patagonicus (95), M. saturninus (88), M. triurus (152), and M. dorsalis (7). We measured the following variables: culmen length, bill height and width, tarsus length, middle toe length, wing chord and tail length. Measurements were generally larger in males than in females except for bill width in M. saturninus and M. triurus, culmen length in M. thenca and M. dorsalis, and bill height in M. dorsalis. There were significant differences between sexes in wing chord for M. patagonicus, M. saturninus and M. triurus; tail length for M. patagonicus and M. triurus; tarsus length for M. patagonicus; and in middle toe length for M. triurus. No significant differences in measurements were found between sexes for M. thenca. Significant discriminant functions were obtained for M. patagonicus, M. saturninus and M. triurus, with a percentage of correct classification less than 80%. Only a few variables were useful for sex determination in the studied Mimus species, i.e. wing chord, tail length, middle toe length and tarsus length for three, two, one and one species, respectively.